IC 9423 Comparison Of Small Mines And Small Businesses: Health And Safety Barriers And Intervention Strategies - Lynn L. Rethi (The National Institute for Occupational Safety and Health (NIOSH), 1995)
This U.S. Bureau of Mines report summarizes common obstacles found when attempting to implement health and safety strategies in small mines and small businesses in general industry. Recently, the U.S. Mine Safety and Health Administration focused much of its attention on addressing health and safety issues at small mines. Some of the more innovative interventions practiced by small businesses in general industry are discussed for consideration of their applicability to the mining industry. The most effective intervention strategy that was developed for small businesses is the Occupational Safety and Health Administration Consultative Program. The details of this program and other intervention strategies used by small mines and small businesses are presented.